THE DEVELOPMENT OF AUGMENTED REALITY(AR) LEARNING MEDIA ON SOLAR SYSTEM MATERIAL FOR GRADE VII (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2024)
Augmented Reality-based learning media is an innovation in teaching and learning activities. Augmented Reality has the advantage of combining objects with the real world, creating new quality and experiences for students. The objective of this research was to create Augmented Reality-based learning media on Solar System material and to determine its validity and practicality. This research was a development study using the 4D Thiagarajan model but without conducting the Disseminate stage. The research subjects were media experts, material experts, teachers, and students. Data collection used validation instruments and student responses with a Likert scale of 1-4. The evaluation results from material experts, media experts, and teachers (users) achieved an average validity of 91%, which was categorized as very valid. The results of the small-scale test of the Augmented Reality-based learning media obtained an average of 78%, categorized as fairly practical. The results of the large group trial obtained an average of 88%, categorized as very practical. Therefore, the Augmented Reality learning media on the Solar System material was deemed suitable for use in seventh-grade classrooms.